The extreme mutator effect of Escherichia coli mutD5 results from saturation of mismatch repair by excessive DNA replication errors. - Schaaper, R M (1989)
Escherichia coli mutator mutD5 is the most potent mutator known. The mutD5 mutation resides in the dnaQ gene encoding the proofreading exonuclease of DNA polymerase III holoenzyme. It has recently been shown that the extreme mutability of this strain results, in addition to a proofreading defect, from a defect in mutH, L, S-encoded postreplicational DNA mismatch repair. The following measurements of the mismatch-repair capacity of mutD5 cells demonstrate that this mismatch-repair defect is not structural, but transient. mutD5 cells in early log phase are as deficient in mismatch repair as mutL cells, but they become as proficient as wild-type cells in late log phase. Second, arrest of chromosomal replication in a mutD5-dnaA(Ts) strain at a nonpermissive temperature restores mismatch repair, even from the early log phase of growth. Third, transformation of mutD5 strains with multicopy plasmids expressing the mutH or mutL gene restores mismatch repair, even in rapidly growing cells. These observations suggest that the mismatch-repair deficiency of mutD strains results from a saturation of the mutHLS-mismatch-repair system by an excess of primary DNA replication errors due to the proofreading defect.